Identification of the safe(r) by design alternatives for nanosilver-enabled wound dressings - Cazzagon, V.; Giubilato, E.; Bonetto, A.; Blosi, M.; Zanoni, I.; Costa, A. L.; Vineis, C.; Varesano, A.; Marcomini, A.; Hristozov, D.; Semenzin, E.; Badetti, E. (Frontiers in Bioengineering and Biotechnology, 2022)
The use of silver nanoparticles (NPs) in medical devices is constantly increasing due to their excellent antimicrobial properties. In wound dressings, Ag NPs are commonly added in large excess to exert a long-term and constant antimicrobial effect, provoking an instantaneous release of Ag ions during their use or the persistence of unused NPs in the wound dressing that can cause a release of Ag during the end-of-life of the product. For this reason, a Safe-by-Design procedure has been developed to reduce potential environmental risks while optimizing functionality and costs of wound dressings containing Ag NPs. The SbD procedure is based on ad-hoc criteria (e.g., mechanical strength, antibacterial effect, leaching of Ag from the product immersed in environmental media) and permits to identify the best one among five pre-market alternatives. A ranking of the SbD alternatives was obtained and the safer solution was selected based on the selected SbD criteria. The SbD framework was also applied to commercial wound dressings to compare the SbD alternatives with products already on the market. The iterative procedure permitted to exclude one of the alternatives (based on its low mechanical strength) and proved to be an effective approach that can be replicated to support the ranking, prioritisation, and selection of the most promising options early in the innovation process of nano-enabled medical devices as well as to encourage the production of medical devices safer for the environment.